Implementasi Program Generasi Berencana Badan Kependudukan dan Keluarga Berencana Nasional di Kecamatan Kenjeran Kota Surabaya - Anette Evania Setyoningtyas Sjahrinal; Dewi Casmiwati (Public Administration Dept, Faculty of Social and Political Science, 2024)
The Generation Planned Program (GenRe) is a government policy that is responsible for overcoming population problems. It is one of the government's efforts in carrying out population development, in order to support Indonesian youth to be more visionaire. This study aims to determine the implementation of the Generation Planning program (Genre) of the East Java Province BKKBN in Kenjeran District, Surabaya City and what factors support and hinder the implementation the program in Kenjeran District, Surabaya City. This study used qualitative research methods. The data used are primary and secondary data. The data that has been processed is then presented in the form of a description, then interpreted or interpreted to be discussed and analyzed qualitatively, then to draw a conclusion. Based on the results of the research and discussion, it is known that the implementation of the Generation Planning Program (GenRe) in Kenjeran District, Surabaya City has been going quite well, although there are still factors that hinder its implementation in the field. This is found in the interpretation aspect in which the understanding of the target group is not comprehends. They don’t feel the benefits of the existence of the GenRe program. It is causes by the impact of the program cannot be felt instantly, and requires a long period of time. In this case the researcher provides recommendations for the government institutions involves need to improve communication in the form of direct counseling and by utilizing social media.